Equity, efficiency, and the U.S. corporation income tax - Ballentine, J. Gregory (Washington, D.C. : American Enterprise Institute for Public Policy Research, 1980)
The author examines the little-understood effects of the corporation income tax,a mainstay of the U.S federal revenue system
Bibliography: p. 102-111.
obn 23/01/2019
Loans
Keywords: Corporations- taxation; Tax incidence; Tax policy; Corporate income tax; United States